STRATEGI MEMBANGUN SINERGI ANTAR SUB TERMINAL AGRIBISNIS (STA) DI PROVINSI BALI - DWI PUTRA DARMAWAN; I DEWA GEDE RAKA SARJANA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2007)
ABSTRACT The result of comprehensiveness measurement performance of Agribusiness Sub Terminal (namely STA) by Balanced Scorecard techniques indicated that the individual of STA own strengths, weaknesses, opportunities and threats in the efforts of improving customer values, processing product with good quality, build customer loyalty, and improve performance of STA financial. The diversify claim concrete effort to build synergism of business partnership to improve effective and efficiency of commodity system of food crop and horticulture. The Objectives of this research is to analyze competitiveness position of group and individual of STA, and formulate build synergy strategy of business partnership between STA in Bali Province. The research result indicate that the competitiveness position of group STA be at growth quadrant, while the competitiveness position of individual STA gone the round of the cell with fascination of middle business strength and industrial attractiveness. In the long run, the competitiveness position of individual STA expected reaching the cell with strong industrial attractiveness and business strength. Therefore, the repair of managerial quality were needed through effort of improvements of market share and quality of product continually, competitive price of product, and also improvement of human resource quality of each STA. According to matrix of synergy, the research shows that attainment of synergy between STA in this time still not yet adequate. In the future, the attainment of synergy between STA expected earn better, with interest settle cooperation between STA in the cases of marketing, operation, management and investment. Key words: To build synergy strategy, Agribusiness Sub Terminal ABSTRAK Hasil pengukuran kinerja STA yang komprehensif dengan Balanced Scorecard menunjukkan bahwa individu STA memiliki keunggulan, kelemahan, peluang dan ancaman sendiri-sendiri dalam upaya meningkatkan customer value, memproses produk yang berkualitas, memuaskan pelanggan, serta meningkatkan kinerja finansial STA. Keragaman tersebut menuntut upaya konkrit untuk membangun sinergisme kemitraan usaha guna meningkatkan efektifitas dan efisiensi sistem komoditas tanaman pangan dan hortikultura tersebut. Hasil penelitian menunjukkan bahwa posisi bersaing kelompok STA saat ini berada pada kuadran pertumbuhan (growth), sedangkan posisi bersaing individu STA tersebar pada sel dengan daya tarik industri dan kekuatan bisnis menengah. Dalam jangka panjang, posisi bersaing individu STA diharapkan dapat mencapai sel dengan daya tarik industi dan kekuatan bisnis yang kuat. Oleh karena itu, perbaikan kualitas manajerial dibutuhkan melalui upaya perbaikan pangsa pasar dan kualitas produk yang berkelanjutan, harga produk yang kompetitif serta perbaikan kualitas SDM masing-masing STA. Berdasarkan matriks sinergi pencapaian sinergi antar STA saat ini belum memadai dan pada masa yang akan datang pencapaian sinergi tersebut diharapkan akan lebih baik dengan lebih memantapkan kerjasama antar STA dalam hal pemasaran, operasi, manajemen, dan investasi. Kata kunci: Strategi Membangun Sinergi, Sub Terminal Agribisnis